2020
DOI: 10.1177/1098612x20939828
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography in cats with cholestatic liver disease

Abstract: Objectives While thromboelastography (TEG) has helped define a complex state of hemostasis in dogs and humans with hepatobiliary disease, it has not been explored in cats with cholestatic liver disease (CLD). The objective of this study was to describe TEG parameters in cats with CLD and to compare these parameters with conventional plasma-based coagulation tests, white blood cell (WBC) count and biochemical indicators of liver disease grade and severity. Methods Eighteen cats with CLD, defined by a serum bili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Coagulation factors II, VII, IX and X as well as anticoagulant mediators including protein C and protein S all require vitamin K to become active; therefore, vitamin K deficiency mediated hypocoagulability has potential to develop in cats, as it does in humans (Harvey 2012). Results from one recent study found that 28% (5/18) of cats with cholestatic liver disease were hyperfibrinolytic (Kakar et al 2020). Minimum coagulation tests that should be performed include prothrombin time, activated partial thromboplastin time and platelet count.…”
Section: Neutrophilic Cholangitis/ Cholangiohepatitismentioning
confidence: 99%
See 2 more Smart Citations
“…Coagulation factors II, VII, IX and X as well as anticoagulant mediators including protein C and protein S all require vitamin K to become active; therefore, vitamin K deficiency mediated hypocoagulability has potential to develop in cats, as it does in humans (Harvey 2012). Results from one recent study found that 28% (5/18) of cats with cholestatic liver disease were hyperfibrinolytic (Kakar et al 2020). Minimum coagulation tests that should be performed include prothrombin time, activated partial thromboplastin time and platelet count.…”
Section: Neutrophilic Cholangitis/ Cholangiohepatitismentioning
confidence: 99%
“…Minimum coagulation tests that should be performed include prothrombin time, activated partial thromboplastin time and platelet count. Thromboelastography should be performed if available because it might more accurately predict haemostatic disorders than conventional coagulation testing alone (Kakar et al 2020).…”
Section: Neutrophilic Cholangitis/ Cholangiohepatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperfibirinolysis is a syndrome characterised by enhanced fibrinolysis that results in premature clot lysis and haemorrhage. One recent study found that 28% (5/18) of cats with cholestatic liver disease were hyperfibrinolytic (Kakar et al 2020). Whether or not this hyperfibrinolytic state occurs in dogs with GBM has not been investigated.…”
Section: Gall Bladder Mucocelementioning
confidence: 99%
“…One recent study found that 28% (5/18) of cats with cholestatic liver disease were hyperfibrinolytic (Kakar et al . 2020). Whether or not this hyperfibrinolytic state occurs in dogs with GBM has not been investigated.…”
Section: Gall Bladder Mucocelementioning
confidence: 99%